Review of Policies and Frameworks on Climate Change, Agriculture, Food and Nutrition Security in Eastern Africa: Ethiopia, Kenya, Rwanda, Tanzania, and Uganda - Radeny, Maren A.O.; Amwata, Dorothy; Hunt, Sarah; Mungai, Catherine; Tumbo, Madaka; Eshetu, Zewdu; Tolo, Casim A.; Butare, Louis; Auma, Joseph; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
This is a review of policies, strategies, and frameworks related to climate change, agriculture, food, and nutrition security in Ethiopia, Kenya, Rwanda, Tanzania, and Uganda. The five focus countries have made tremendous efforts to strengthen the enabling environment for addressing climate change and improving agricultural productivity and food and nutrition security by putting the appropriate policies, frameworks, and strategies in place. This policy review was based on document review and expert consultations in each country and specifically: i) analyzed the policy integration between climate change and agriculture and food and nutrition security for each country, and ii) examined the institutional landscape for climate change, agriculture, food, and nutrition security Eastern Africa. There are deliberate and proactive efforts to strengthen the integration and coherence in the more recent policies and frameworks for climate change, agriculture, food, and nutrition security. Most East African countries have prioritized agricultural productivity, food availability, and climate change adaptation in most of their policies and frameworks, with a narrow focus on food utilization and climate change mitigation. However, little effort has been made to integrate budgeting and planning, implementation and monitoring processes, bringing together climate change and agriculture, and food and nutrition security. There is a need to strengthen the linkages and coordination between climate change and agriculture, food and nutrition stakeholders to improve efficiency and reduce overlaps in implementing programs and projects.